2022
DOI: 10.3389/feart.2022.832650
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation Study on Dust Suppression Mechanism of Burning Rock Blasting in Open-Pit Mine

Abstract: In an open-pit mine in Xinjiang, part of the stripped area is covered by burnt rock. Due to the low strength and fragility of burnt rock, dust is more easily generated during blasting. Taking the mining area as the research background, the mechanical property parameters of burnt rock were tested, and the blasting parameter design of on-site operation was understood. The blasting numerical simulation of burnt rock step was carried out by using a numerical simulation software (LS-DYNA). From the angle of stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Jia, Z.Z. et al [10] used (LS-DYNA) to perform blasting of a coke rock bench Numerical simulations, from rock stress perspective, stress clouds and stress curves from numerical simulations, concluded that the root cause of the high dust production from blasting operations was the excessive fragmentation of the coke rocks after the blast wave, and the excessive blast energy was converted into kinetic energy to drive the dust to escape. Song, Y. q. et al [11,12] conducted dynamic compression tests on lignite with different impact rates, and the results showed that the increase in strain rate had a significant hardening effect on the dynamic mechanical parameters of the rock samples, and the stress-strain curve had an obvious "double-peak" feature; meanwhile, macroscopic cracks in the rock appeared at the first stress peak and disappeared after further compression until interlaminar fracture occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Jia, Z.Z. et al [10] used (LS-DYNA) to perform blasting of a coke rock bench Numerical simulations, from rock stress perspective, stress clouds and stress curves from numerical simulations, concluded that the root cause of the high dust production from blasting operations was the excessive fragmentation of the coke rocks after the blast wave, and the excessive blast energy was converted into kinetic energy to drive the dust to escape. Song, Y. q. et al [11,12] conducted dynamic compression tests on lignite with different impact rates, and the results showed that the increase in strain rate had a significant hardening effect on the dynamic mechanical parameters of the rock samples, and the stress-strain curve had an obvious "double-peak" feature; meanwhile, macroscopic cracks in the rock appeared at the first stress peak and disappeared after further compression until interlaminar fracture occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Cui 9 , a new method using water-silt composite blasting is presented, which improves the rock fragmentation rate, reduces rock buildup, lowers dust, and saves explosives. Jia et al 10 carried out numerical simulation of blasting on coke rock steps using (LS-DYNA) and concluded that the root cause of the high dust production from blasting operations is the excessive fragmentation of coke rock after the blast wave action. Song, et al 11 , 12 conducted dynamic compression tests on lignite with different impact velocities, and the results showed that the increase of strain rate had a significant hardening effect on the dynamic mechanical parameters of the rock samples.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms for roof water inrush are different case to case. 3 , 6 − 8 One main mechanism for the water inrush is the roof failure after coal seam mining, which is thoroughly explored by scholars. 9 − 14 The major research method is conducting a similar model test.…”
Section: Introductionmentioning
confidence: 99%
“…Many types of roof water disasters are recognized in Jurassic coalfields, such as separated strata water disasters, water inrush, and sand inrush, roof thick sandstone water disasters, burning rock water disasters, etc. The mechanisms for roof water inrush are different case to case. ,− One main mechanism for the water inrush is the roof failure after coal seam mining, which is thoroughly explored by scholars. The major research method is conducting a similar model test. However, the experimental conditions are way different from the actual conditions in the mine, which makes the results less convincing. What is more, the geological conditions, hydrogeological conditions, lithology, and mining conditions are different from one mining area to another mining area, the research results cannot be widely applied, and the existing conclusions are not suitable for the Liangshuijing coal mine.…”
Section: Introductionmentioning
confidence: 99%